2012
DOI: 10.30638/eemj.2012.264
|View full text |Cite
|
Sign up to set email alerts
|

Demarcation of Protection Perimeters for Surface Waters of Taabo (Ivory Coast) Watershed Using Gis and Multicriteria Analysis

Abstract: The lake system of Taabo watershed contributes at 35% in the country electrification. Besides this use, water is also used in agriculture, fishing and for drinking water. The increasing human activities in its basin led to siltation of Kossou's Lake and eutrophication of 26% of Taabo's Lake total area. However, no study has yet been performed to protect or prevent this resource against pollution. This study is the first in Ivory Coast intending to delineate three protection areas around the watershed lakes. It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…This may also cause the conductivity of the water to rise, reduce dissolved oxygen posing danger to aquatic organisms in the water. Another source of surface water pollution is the gradual evolution of sediment (ANOH et al 2012) and this may require dredging to restore its depth. Iron ore mining in Liberia and India was found to be potential contamination of surface water and groundwater (GLEEKIA and SAHU, 2016).…”
Section: Water Pollutionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may also cause the conductivity of the water to rise, reduce dissolved oxygen posing danger to aquatic organisms in the water. Another source of surface water pollution is the gradual evolution of sediment (ANOH et al 2012) and this may require dredging to restore its depth. Iron ore mining in Liberia and India was found to be potential contamination of surface water and groundwater (GLEEKIA and SAHU, 2016).…”
Section: Water Pollutionmentioning
confidence: 99%
“…They therefore proposed expansion of water quality monitoring to other sources of water and not only on pipe water. Identification of lakes vulnerability areas of pollution can help in taking immediate steps to curb the pollution (ANOH et al 2012). NARE et al (2011) suggested community participation in the monitoring and management of rivers and lakes.…”
Section: Water Pollutionmentioning
confidence: 99%
“…The vulnerability of a surface water to pollution depends on several parameters including slope, soil type, land use, runoff, density of the watershed network (Ake et al, 2020;Ake et al, 2019;Anoh et al, 2012Anoh et al, , 2018Macary et al, 2010).…”
Section: Assessment Of Vulnerability To Pollution Of Lagoonsmentioning
confidence: 99%
“…In fact, the setting up of priorities allows Table 2. Scale of several parameters opposite to infiltration (Haouchine et al, 2010 to synthetize our appreciations from a mathematical view in order to check their coherences (Anoh et al, 2012).…”
Section: ) Drainage Densitymentioning
confidence: 99%